Role of protein phosphatases PP1, PP2A, PP4 and Cdc14 in the DNA damage response - Facundo Ramos; María Teresa Villoria; Esmeralda Alonso‐Rodríguez; Andrés Clemente‐Blanco (2019)
Maintenance of genome integrity is fundamental for cellular physiology. Our hereditary information encoded in the DNA is intrinsically susceptible to suffer variations, mostly due to the constant presence of endogenous and environmental genotoxic stresses. Genomic insults must be repaired to avoid loss or inappropriate transmission of the genetic information, a situation that could lead to the appearance of developmental anomalies and tumorigenesis. To safeguard our genome, cells have evolved a series of mechanisms collectively known as the DNA damage response (DDR). This surveillance system regulates multiple features of the cellular response, including the detection of the lesion, a transient cell cycle arrest and the restoration of the broken DNA molecule. While the role of multiple kinases in the DDR has been well documented over the last years, the intricate roles of protein dephosphorylation have only recently begun to be addressed. In this review, we have compiled recent information about the function of protein phosphatases PP1, PP2A, PP4 and Cdc14 in the DDR, focusing mainly on their capacity to regulate the DNA damage checkpoint and the repair mechanism encompassed in the restoration of a DNA lesion.